Empowering Emotion: The Driving Force of Share and Purchase Intentions in Viral Advertising. Issue 1 (2nd January 2022) - Wen, Taylor Jing; Choi, Chang Won; Wu, Linwan; Morris, Jon D.
ABSTRACT: This research adopts the PAD model of emotions (i.e., pleasure–arousal–dominance) and conducts two survey studies to empirically test the role of emotions in viral advertising. Study 1 confirms the positive role of pleasure, arousal, and dominance in making a video commercial spread virally. Results demonstrate that dominance is the strongest predictor among the three dimensions to explain increased share and purchase intentions. More importantly, Study 2 shows that psychological empowerment is the underlying mechanism that explains the effects of dominance on both share and purchase intentions. Theoretical and practical implications are discussed.